The Effect of Shear Span on the Behavior of Triangularly Corrugated Web Steel Girders - Mazin Diwan Abdullah; Abdulamir Atalla Almayah (Civil Engineering Journal, 2023)
Built-up steel girders have many applications in structural engineering, both in bridges and buildings. Flat web steel girders, which are the traditional choice, involve several weaknesses. Girders with corrugated webs were found to be more effective in their load-carrying capacity and deflection than girders with flat webs. In light of this, an effort is made in this work to examine how the addition of triangular corrugated webs influences the load-bearing capacity and deflection of steel girders. This study aimed to determine whether or not the strength of built-up steel with corrugated webs could be improved. A concentrated midspan load was applied to six simply supported steel beams of varying span-to-depth ratios (1.0, 1.833, and 2.5) and web corrugation amplitudes (30 and 60 mm). An increase in ultimate strength of 15.7% to 35.1% was found for webs with triangular corrugations of 30 mm and from 2% to 29.1% for webs with corrugations of 60 mm. A reduction in deflection of up to 35.3% can be attained when using triangular corrugated webs. It was also found that using webs with 30 mm corrugations was more efficient than using webs with 60 mm corrugations. The effect of corrugation was found to fade when the span-to-depth ratio increased to 2.5. This led to the conclusion that using webs of 30 mm amplitude of triangular corrugation could improve the strength and serviceability of steel girders. Doi: 10.28991/CEJ-2023-09-02-09 Full Text: PDF